2016
DOI: 10.1369/0022155416656349
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondiiInfection Promotes Epithelial Barrier Dysfunction of Caco-2 Cells

Abstract: SummaryAfter oral infection, Toxoplasma gondii invades intestinal cells, induces breakdown of intestinal physiology and barrier functions, and causes intestinal pathology in some animal species. Although parasites' invasion into host cells is a known phenomenon, the effects of T. gondii infection in the intestinal barrier are still not well established. To evaluate morphological and physiological modifications on the colorectal adenocarcinoma-derived Caco-2 cell line during T. gondii infection, microvilli, tig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 47 publications
2
32
0
1
Order By: Relevance
“…They include a paracellular route (Barragan et al, 2005;Barragan & Sibley, 2002;Furtado et al, 2012;Weight, Jones, Horn, Wellner, & Carding, 2015) passing cellular TJs and a transcellular route (Dubey, 1997;Konradt et al, 2016;Lambert & Barragan, 2010). Additionally, parasitised leukocytes may aid in direct translocation (Courret et al, 2006;Lachenmaier et al, 2011) or by depositing parasites on the endothelium (Lambert & Barragan, 2010), FIGURE 7 Hypothetical model for the impact of focal adhesion kinase (FAK) dysregulation on the transmigration of Toxoplasma gondii across cellular barriers(I) Extracellular T. gondii tachyzoites can cross endothelial and epithelial barriers (primary MBECs, human retinal endothelial cells, bEnd.3, Caco2, mouse and rat intestinal epithelial cells m-IC cl12 and IEC-6, respectively, and MDCKs) by a paracellular route involving interactions with cell adhesion molecules and intercellular TJ proteins (Barragan et al, 2002;Barragan et al, 2005;Furtado et al, 2012;Weight et al, 2015;Briceno et al, 2016). Additionally, parasitised leukocytes may aid in direct translocation (Courret et al, 2006;Lachenmaier et al, 2011) or by depositing parasites on the endothelium (Lambert & Barragan, 2010), FIGURE 7 Hypothetical model for the impact of focal adhesion kinase (FAK) dysregulation on the transmigration of Toxoplasma gondii across cellular barriers(I) Extracellular T. gondii tachyzoites can cross endothelial and epithelial barriers (primary MBECs, human retinal endothelial cells, bEnd.3, Caco2, mouse and rat intestinal epithelial cells m-IC cl12 and IEC-6, respectively, and MDCKs) by a paracellular route involving interactions with cell adhesion molecules and intercellular TJ proteins (Barragan et al, 2002;Barragan et al, 2005;Furtado et al, 2012;Weight et al, 2015;Briceno et al, 2016).…”
Section: Pharmacological Inhibition Of Fak Modestly Alters Barrier mentioning
confidence: 99%
See 1 more Smart Citation
“…They include a paracellular route (Barragan et al, 2005;Barragan & Sibley, 2002;Furtado et al, 2012;Weight, Jones, Horn, Wellner, & Carding, 2015) passing cellular TJs and a transcellular route (Dubey, 1997;Konradt et al, 2016;Lambert & Barragan, 2010). Additionally, parasitised leukocytes may aid in direct translocation (Courret et al, 2006;Lachenmaier et al, 2011) or by depositing parasites on the endothelium (Lambert & Barragan, 2010), FIGURE 7 Hypothetical model for the impact of focal adhesion kinase (FAK) dysregulation on the transmigration of Toxoplasma gondii across cellular barriers(I) Extracellular T. gondii tachyzoites can cross endothelial and epithelial barriers (primary MBECs, human retinal endothelial cells, bEnd.3, Caco2, mouse and rat intestinal epithelial cells m-IC cl12 and IEC-6, respectively, and MDCKs) by a paracellular route involving interactions with cell adhesion molecules and intercellular TJ proteins (Barragan et al, 2002;Barragan et al, 2005;Furtado et al, 2012;Weight et al, 2015;Briceno et al, 2016). Additionally, parasitised leukocytes may aid in direct translocation (Courret et al, 2006;Lachenmaier et al, 2011) or by depositing parasites on the endothelium (Lambert & Barragan, 2010), FIGURE 7 Hypothetical model for the impact of focal adhesion kinase (FAK) dysregulation on the transmigration of Toxoplasma gondii across cellular barriers(I) Extracellular T. gondii tachyzoites can cross endothelial and epithelial barriers (primary MBECs, human retinal endothelial cells, bEnd.3, Caco2, mouse and rat intestinal epithelial cells m-IC cl12 and IEC-6, respectively, and MDCKs) by a paracellular route involving interactions with cell adhesion molecules and intercellular TJ proteins (Barragan et al, 2002;Barragan et al, 2005;Furtado et al, 2012;Weight et al, 2015;Briceno et al, 2016).…”
Section: Pharmacological Inhibition Of Fak Modestly Alters Barrier mentioning
confidence: 99%
“…The transcellular route implies that parasites enter from the apical side of the cell and exit from the basolateral side after replication, eg, bradyzoites in enterocytes and tachyzoites in brain endothelium. Additionally, parasitised leukocytes may aid in direct translocation (Courret et al, 2006;Lachenmaier et al, 2011) or by depositing parasites on the endothelium (Lambert & Barragan, 2010), FIGURE 7 Hypothetical model for the impact of focal adhesion kinase (FAK) dysregulation on the transmigration of Toxoplasma gondii across cellular barriers(I) Extracellular T. gondii tachyzoites can cross endothelial and epithelial barriers (primary MBECs, human retinal endothelial cells, bEnd.3, Caco2, mouse and rat intestinal epithelial cells m-IC cl12 and IEC-6, respectively, and MDCKs) by a paracellular route involving interactions with cell adhesion molecules and intercellular TJ proteins (Barragan et al, 2002;Barragan et al, 2005;Furtado et al, 2012;Weight et al, 2015;Briceno et al, 2016). (II) T. gondii can alternatively transmigrate across cellular barriers by invading at the apical side and exiting at the basolateral side, after replication in the parasitophorous vacuole (PV) (Dubey, 1997;Konradt et al, 2016).…”
Section: Gene Silencing Of Fak (Ptk-2) Dysregulates Barrier Integrimentioning
confidence: 99%
“…Indeed, the gut targeted inflammatory state elicited by T. gondii has been adapted for experimental animal models of inflammatory bowel diseases and of ileitis in particular, although evidence in support of cellular pathologies in the duodenum and jejunum is surfacing as well (Araujo et al, 2015; Trevizan et al, 2016). The intra- and para-cellular mechanisms for parasite invasion of gut epithelial or Peyer’s patch-associated cells are not known with certainty but are actively investigated topics (Briceno et al, 2016; Gregg et al, 2013). …”
Section: Toxoplasma and Intestinal Inflammationmentioning
confidence: 99%
“…The results showed that the trophozoites and their CM produced a substantial cytopathic effect and an important decrease of TEER in the RBMEC culture. Previous reports showed that the cytopathic damage produced by A. castellanii, E. histolytica, Toxoplasma gondii, and Giardia duodenalis in HBMEC and MDCK cells, was the result of the action of their proteases (Betanzos et al 2013;Briceno et al 2016;Cuellar et al 2017;Halliez et al 2016;Khan and Siddiqui 2009;Shibayama et al 2013). To evaluate the damage produced by the amoebic proteases, we preincubated the trophozoites and their CM with E-64 or Aprotinin and observed that the cysteine proteases inhibitor but not the serine proteases exerted a protective effect on the endothelial monolayer.…”
Section: Discussionmentioning
confidence: 97%